"The things that attach people": a critical literary analysis of the fiction of Barbara Kingsolver - Gorton, Ceri Martha (2009)
This is the first full-length scholarly work dedicated to the fiction of Kentucky-raised feminist activist and trained biologist Barbara Kingsolver. Interrogating the political efficacy of the work of an author who proclaims that art “should be political” and that “literature should inform as well as enlighten”, this thesis explores the ways in which Kingsolver positions herself variously as an environmentalist, liberal, communitarian, feminist and agrarian. It unpacks the author’s issues-based approach to writing fiction and its effect on her commercial popularity and through close readings of her fiction provides an assessment of this popular and critically acclaimed contemporary American writer.